Interictal Discharge Pattern in Preschool-Aged Children With Tuberous Sclerosis Complex Before and After Resective Epilepsy Surgery - Yuan, Liu; Wang, Yangshuo; Cheng, Shuhua; Zhang, Junchen; Zhang, Shaohui; Liu, Tinghong; Zhang, Guojun; Liang, Shuli (Frontiers in Neurology, 2022)
To analyze the interictal discharge (IID) patterns on preoperative scalp electroencephalogram (EEG) and compare the changes in IID patterns after removal of epileptogenic tubers in preschool children with tuberous sclerosis complex (TSC)-related epilepsy, 35 preschool children who underwent resective surgery for TSC-related epilepsy were enrolled retrospectively, and their EEG data were collected before surgery to 3 years after surgery. Twenty-three (65.7%) patients were seizure-free postoperatively at 1-year follow-up. All preoperative scalp EEGs presented with IIDs. IID patterns on preoperative scalp EEGs did not influence the outcomes of postoperative seizure controls, while patients with focal IIDs or generalized IID patterns on preoperative EEG presented a high percentage of normal postoperative scalp EEGs. Patients with non-IID and focal IID on postoperative EEGs were likely to achieve postoperative seizure freedom. Significant differences were not found in the postoperative seizure controls among the patients with different postoperative IID patterns on the resected areas at 1–3 years of follow-ups, while patients with new focal IIDs presented a significantly lower percentage of seizure freedom than those without new focal IIDs on postoperative EEGs at 3-year follow-up. In conclusion, 37%–40% of postoperative patients rendered non-IID on scalp EEGs, and patients with postoperative seizure freedom were more likely to have non-IIDs on postoperative EEGs. New focal IIDs were negative factors for seizure freedom at the 3-year follow-up. The IID patterns on preoperative scalp EEGs were consistent, and epileptogenic tubers in patients with TSC-related epilepsy were relatively stable.